Acute toxicity of chemotherapy in central nervous system germ cell tumour patients according to age - Palenzuela, Gilles; Schiffler, Camille; Frappaz, Didier; Peyrl, Andreas; Gerber, Nicolas U.; Kortmann, Rolf-Dieter; Philippe, Michael; Zimmermann, Martin; Murray, Matthew J.; Nicholson, James C.; Calaminus, Gabriele; Faure-Conter, Cécile (Frontiers in Oncology, 2024)
Background: SIOP-CNS-GCT-II European trial was opened for the treatment of patients of any age with central nervous system germ cell tumour (CNS-GCT). Four courses of preirradiation chemotherapy were delivered. The influence of patient age on chemotherapy related acute toxicity (CRAT) was assessed.Methods: CRAT was analysed according to age-groups: children (aged ≤11 years), adolescents (aged 12-17 years), adults (aged ≥18 years) and to chemotherapy type: CarboPEI (alternating etoposide-carboplatin/etoposide-ifosfamide) for non-metastatic germinoma; PEI (cisplatinetoposide-ifosfamide) for standard-risk non-germinomatous GCT (NGGCT); PEI and highdose PEI (HD-PEI), for high-risk or poorly responsive NGGCTs.Results: 296 patients were assessabled for CRAT: 105 children, 121 adolescents, 70 adults (max age: 41 years). Median cumulative doses/m² of chemotherapy were similar among agegroups. The proportion of germinoma over NGGCT (and accordingly use of CarboPEI chemotherapy) was higher in the adult groups (79%) versus the other two groups (62%). Delay in chemotherapy ≥7 days was noticed in 27%, 38%, and 19% of children, adolescents, and adults, respectively. Grade ≥3 haematological and non-haematological adverse events (AEs) were observed in 94%/31%, 97%/36%, and 77%/21% of children, adolescents, and adults, respectively. No toxic death was reported. Grade ≥3 AEs and delayed chemotherapies were significantly rarer in adults when compared with adolescents, even when adjusted on chemotherapy type: odds ratio: 0.1 [95%CI 0.02-0.4], and 0.2 [95%CI 0.1-0.4] in the group treated with CarboPEI.Adult patients can be treated safely with a chemotherapy intensive protocol, with even less toxicity than that observed in adolescents. Further work is required to understand agerelated differences regarding toxicity.